High-dose dual therapy versus culture-based susceptibility-guided therapy as a rescue regimen for Helicobacter pylori infection: a randomized controlled trial. (December 2022) - Zhao, Zhe; Zou, Pei-Ying; Su, Na-Yun; Guo, Yan; Wang, Xing-Wei; Zhao, Jing-Tao; Mei, Hao; Shi, Qing; Wang, Bin; Chen, Dong-Feng; Lan, Chun-Hui
Background: Although the Maastricht VI/Florence consensus report recommended high-dose proton pump inhibitor–amoxicillin dual therapy as possible rescue therapy for Helicobacter pylori infection, clinical evidence of its efficacy was lacking. Objectives: To compare the efficacy, safety, patient compliance, and cost between high-dose dual therapy (HDDT) and culture-based susceptibility-guided therapy (CB-SGT) as a rescue regimen for H. pylori infection. Design: A single-center, open-label, randomized controlled clinical trial. Methods: In all, 146 patients with a history of eradication failure were enrolled and randomly assigned to receive HDDT or CB-SGT. HDDT consisted of esomeprazole 20 mg and amoxicillin 750 mg, both given four times per day (qid). CB-SGT consisted of esomeprazole 20 mg twice daily (bid), amoxicillin 1000 mg bid plus clarithromycin 500 mg bid, metronidazole 400 mg bid, or levofloxacin 500 mg daily (qd) for sensitive patients, in that order. For patients with triple resistance, a bismuth-containing regimen with a high dose of metronidazole was chosen, including esomeprazole 20 mg bid, bismuth 220 mg bid, amoxicillin 1000 mg bid, and metronidazole 400 mg qid. All regimens were given for 14 days. Results: The eradication H. pylori rates achieved with HDDT in the intention-to-treat (ITT), per-protocol, and modified ITT analyses were all 84.9% [62/73, 95% confidence interval (CI): 76.5–93.9%], compared with 83.6% (61/73, 95% CI: 74.9–92.3%), 84.7% (61/72, 95% CI: 76.2–93.2%), and 84.7% (61/72, 95% CI: 76.2–93.2%) with CB-SGT, respectively. For patients with CYP2C19 polymorphisms of intermediate/poor metabolizers, the eradication rates of HDDT and CB-SGT were 90.70% (39/43, 95% CI: 77.86–97.41%) and 84.21% (32/38, 95% CI: 68.75–93.98%), respectively. The difference between groups was 6.49% (95% CI: −8.00% to 20.97%), and the non-inferiority p value was 0.0128. For patients with a treatment interval of more than 3 months, the eradication rates of the two regimens reached 88.71% (95% CI: 78.11–95.34%) and 71.97% (95% CI: 70.02–90.64%). The difference between groups was 6.74% (95% CI: −5.71% to 19.20%), with a non-inferiority p value of 0.0042. Patient adherence was high in both groups. The HDDT had a lower cost and rate of side effects ( p < 0.001) compared with CB-SGT. Conclusions: HDDT can reach an eradication rate of 85% in treatment-experienced patients of H. pylori infection and 91% in patients with CYP2C19 polymorphisms of intermediate/poor metabolizers, with good compliance, lower side effects and costs, and less use of antibiotics. In conclusion, HDDT offers an effective rescue regimen for H. pylori infection. Registration: This clinical trial was registered at the Chinese Clinical Trail Registry (trail registration number: ChiCTR1900025044)